Heteroacene-Based Amphiphile as a Molecular Scaffold for Bioimaging Probes - Ranathunge, Tharindu A.; Yaddehige, Mahesh Loku; Varma, Jordan H.; Smith, Cameron; Nguyen, Jay; Owolabi, Iyanuoluwani; Kolodziejczyk, Wojciech; Hammer, Nathan I.; Hill, Glake; Flynt, Alex; Watkins, Davita L. (Frontiers in Chemistry, 2021)
The challenges faced with current fluorescence imaging agents have motivated us to study two nanostructures based on a hydrophobic dye, 6H-pyrrolo[3,2-b:4,5-b’]bis [1,4]benzothiazine (TRPZ). TRPZ is a heteroacene with a rigid, pi-conjugated structure, multiple reactive sites, and unique spectroscopic properties. Here we coupled TRPZ to a tert-butyl carbamate (BOC) protected 2,2-bis(hydroxymethyl)propanoic acid (bisMPA) dendron via azide-alkyne Huisgen cycloaddition. Deprotection of the protected amine groups on the dendron afforded a cationic terminated amphiphile, TRPZ-bisMPA. TRPZ-bisMPA was nanoprecipitated into water to obtain nanoparticles (NPs) with a hydrodynamic radius that was <150 nm. For comparison, TRPZ-PG was encapsulated in pluronic-F127 (Mw = 12 kD), a polymer surfactant to afford NPs almost twice as large as those formed by TRPZ-bisMPA. Size and stability studies confirm the suitability of the TRPZ-bisMPA NPs for biomedical applications. The photophysical properties of the TRPZ-bisMPA NPs show a quantum yield of 49%, a Stokes shift of 201 nm (0.72 eV) and a lifetime of 6.3 ns in water. Further evidence was provided by cell viability and cellular uptake studies confirming the low cytotoxicity of TRPZ-bisMPA NPs and their potential in bioimaging.